Πλινθευτές, κεραμοποιοί και καμίνια στους βυζαντινούς και μεταβυζαντινούς χρόνους - ΓΕΡΟΛΥΜΟΥ Κωνσταντίνα (Byzantina Symmeikta, 2017)
Brickmakers, Tilemakers and Kilns in the Byzantine and Post-Byzantine Periods. Detecting Textual and Iconographic Evidence. Textual sources can add further information to the archaeological evidenc concerning the manufacture and production of bricks and tiles in the Byzantine and post-Byzantine times. Through a variety of texts one can get a better idea about the brick and tile workshops and the production process. As far as the life of craftsmen is concerned, one may partially approach issues, such as their working conditions, payment and social status. In this paper we also attempt to gather and present all terms concerning the brick and tile production, as well as the terms employed for the craftsmen involved in the production. The terms in question appear in hagiographical texts and other written sources. The information revealed in textual sources is further enriched by iconographic evidence, that has not been adequately studied previously.